Distribution of neuronal cells which contain dopamine β‐hydroxylase, tyrosine hydroxylase, neuropeptide Y and vasoactive intestinal polypeptide in the human internal carotid nerve. Issue 5 (15th September 2021) - Sato, Tadasu; Yajima, Takehiro; Kokubun, Souichi; Tachiya, Daisuke; Ichikawa, Hiroyuki
Abstract: The human internal carotid nerve (ICN) occasionally has a swelling beneath the external opening of the carotid canal. In this study, the presence and distribution of neuronal cells were investigated in the bilateral ICNs of nine human cadavers. Among 44.4% of the cadavers, swellings were detected in the ICN. Their diameters ranged from 1.7 to 3.6 mm (average ±  SD  = 2.6 ± 0.7 mm). Thirty‐eight percent of these swellings were large (diameter > 3 mm) and showed an oval shape. The large swelling contained many neuronal cells. However, the ICNs with or without a swelling <3 mm diameter were mostly free from neuronal cells (93.3%). Only in one human cadaver, the right ICN without a swelling had a small number of neuronal cells. By the present immunohistochemical method, ICN neurons contained catecholamine‐synthesizing enzymes and neuropeptides. Dopamine‐beta hydroxylase‐ and tyrosine hydroxylase‐immunoreactivity were mostly expressed by ICN neurons. More than half of them also contained neuropeptide Y‐immunoreactivity. However, vasoactive intestinal polypeptide‐immunoreactive ICN neurons were relatively infrequent. Substance P‐ and calcitonin gene‐related peptide‐immunoreactive ICN neurons could not be detected. By the cell size analysis, neuropeptide Y‐immunoreactive neurons were significantly smaller than neuropeptide Y‐immunonegative neurons in the ICN. The present study suggests that ICN neurons have a sympathetic function in the human.